Comparative toxicity of Butachlor, Imidacloprid andSodium fluoride on protein profile of the walking catfish Clarias batrachus - Vishal Rajput, Santosh Kumar Singh, Arpita,Kirti, Abhishek (Journal of Applied Pharmaceutical Science)
Freshwater cat fish Clarias batrachus was exposed to Butachlor, Imidacloprid and Sodium fluoride with lethal and sub-lethal concentration for 72 hrs and 21 days durations. Protein changes in liver and muscles were analyzed after exposure period. Imidacloprid and sodium fluoride caused remarkable protein loss lethal concentration but at sub-lethal level their toxicity was moderate. But Butachlor caused remarkable protein loss at lethal as well as sublethal conentartion.
Keywords: Protein,Butachlor,Imidacloprid,Sodium fluoride